Presenza ebraica a Bitonto nel XV secolo: notizie dai protocolli del notaio Angelo Benedetto di Bitritto (1458-1486) - Ricci, Vito (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2018)
Notizie di un insediamento ebraico a Bitonto si hanno sin dall’ultimo ventennio del XIII secolo. Nella seconda metà del XV secolo, gli ebrei ebbero il loro momento di splendore nell’intero Mezzogiorno e, per conoscere la loro storia, si rivelano particolarmente utili i registri notarili. A questi documenti si sono accostati, negli scorsi decenni, già diversi studiosi (Carabellese all’inizio del XX secolo, più recentemente Colafemmina e Maiorano), pubblicando alcuni atti, o i loro estratti, dalle carte di alcuni notai operanti a Bitonto. In questo contributo si forniscono nuovi dati relativi agli ebrei locali contenuti nei registri del notaio Angelo Benedetto di Bitritto, in gran parte inediti. Si tratta di 256 documenti che toccano, con varie interruzioni, la presenza ebraica a Bitonto fra il 1458 e il 1486; altri dati mancanti sono stati suppliti dalle fonti a stampa. Gli atti riguardano generalmente attività economiche e risulta ben documentato il coinvolgimento degli ebrei bitontini in vari tipi di commercio (abiti, olio d’oliva, bestiame, spezie, sapone), ma anche in attività di prestito. Sono presenti vari artigiani, ma anche proprietari d’immobili. Speciale attenzione è data, infine, a due gruppi familiari particolarmente influenti, i Rusellus e i Mayr, i cui membri ricoprirono importanti ruoli politici e amministrativi e di cui si è tentato di ricostruire i complessi rapporti familiari. The Jewish presence in Bitonto during the 15th century: knowledge from the registers of notary Angelo Benedetto di Bitritto (1458-1486) The existence of a Jewish settlement in Bitonto dates to the last twenty years of the 13th century. During the second half of the 15th century, Jews there had their period of greatest splendour as in the whole Italian Mezzogiorno. Registers of notary deeds are an helpful source to retrace the history of the Jewish community. In past decades, some scholars (Carabellese at the beginning of the 20th century, Colafemmina and Maiorano more recently) published deeds or their summaries concerning some notaries operating in Bitonto. In this paper, more information is provided on Jews in the Aragonese age using the registers of the notary Angelo Benedetto di Bitritto, most of which are still unpublished (Colafemmina has only published about 10 deeds). There are 256 deeds affecting Jews living in Bitonto from 1458 to 1486, even if they do not cover continuously the whole span; the information from these deeds has been completed with other published sources. The deeds regard especially business, so the main subject of this contribution is the analysis of the Jews’ local economic activities. They were often involved in trade (in clothes, olive oil, cattle, spice and soap), but also in moneylending. Some were craftsmen; others employed their financial resources in real estate, buying and selling houses. The study focuses on two influential Jewish dynasties, the Russellus and the Mayr, whose members had important roles in the political and administrative life of the local Giudecca. The paper also proposes a reconstruction of kinship connections in lineage and describes events regarding the members of their families.